PENYULUHAN STRATEGI DISIPLIN POSITIF ANAK MELALUI PROGRAM PEMBINAAN KARAKTER DI DESA KLAMBIR V KECAMATAN HAMPARAN PERAK - Utami, Rahayu Dwi; Siregar , Bahtiar; Rezeki , Afriya Sri (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2024)
This community service is motivated by the results of observations that show that positive discipline in early childhood is very low in Rizqy Private Kindergarten, Hamparan Perak District. The problem is the unfair treatment of teachers in providing learning to early childhood, which has an impact on low positive discipline. The solution to this problem is to provide interesting methods and media through free play that is related to the independent curriculum, which frees early childhood to express themselves to bring out the interests and talents of each child. The purpose of the media strategy provided is to be able to increase positive discipline in early childhood. The method used in this community service is counseling by providing material exposure to teachers and parents. This method is known to have many positive impacts on the growth and development of early childhood. With various positive discipline strategies provided, it is hoped that it can increase positive discipline in early childhood at Rizqy Private Kindergarten, Klambir V Village, Hamparan Perak District. The result of this community service is the implementation of a character development program to increase positive discipline in early childhood.